Pedagogia do encantamento: o ensino de escrita em Língua Portuguesa - Simka, Sérgio (2017)
This work presents the elaboration of a pedagogy of writing called Pedagogy of Enchantment characterized by a theoretical-methodological-procedural structure, wich aims to make the student become a linguistic self, through linguistic self-esteem, becoming a linguistic self-writer, anchored by an architecture of thinking, saying and acting, whose objective is to develop his linguistic-textual-discursive competence. It was thought as an attempt to change the practice that has been developed on the production of the wrtitten text, wich has presented unsatisfactory result, according to the press findings and testimonials of experts brought by the research. By means of activities applied in the classroom in the light of this Pedagogy, it was possible to notice an improvement in the production of texts of the students